A Lagrangian oil spill transport model for the Red Sea. (1st December 2020) - Periáñez, R.
Abstract: An oil spill model was developed for the Red Sea. It uses detailed data on water circulation: instantaneous tidal currents, tidal residuals (both from a tidal model specifically applied to the Red Sea) and baroclinic circulation derived from HYCOM ocean model. The model can also incorporate forecasts of local (in the spill area) winds. The transport model is Lagrangian and includes advection/diffusion plus specific processes for oil, as buoyancy, decomposition and evaporation. Results of the tidal model were compared with observations in the sea. The transport model was first applied to passive particles to compare the significance in advective processes of the components of the current (tidal, tidal residual, baroclinic currents) over several areas and seasons and then it was applied to some oil spills: the model output was compared with results from previous simulations and it was also applied to hypothetical oil spills. Highlights: A new Lagrangian model for oil spill transport model developed for the Red Sea. It includes detailed water circulation: tides, tidal residuals and baroclinic currents. Specific processes for oil are included. The model was compared with previous simulations and hypothetical accidents were simulated. It is robust, it is easy to provide input data and to run. Short running times.